The relationship of miR-155 host gene polymorphism in the susceptibility of cancer: a systematic review and meta-analysis - Jin, Gang; Guo, Tao; Liu, Jia-Wei; Yang, Han-Yu; Xu, Jian-Guo; Pang, Yao; Yang, Yi; He, Shao-E.; Yi, Kang (Frontiers in Genetics, 2025)
BackgroundmiR-155 is overexpressed in many cancers, highlighting its potential as a biomarker for cancer diagnosis, treatment, and therapeutic evaluation. miR-155 is processed from the miR-155 host gene (MIR155HG). Genetic variations in MIR155HG may influence cancer susceptibility, but existing evidence is inconclusive. This study aimed to evaluate the association of MIR155HG polymorphisms with cancer risk.Material/MethodsA systematic literature search identified 15 case-control studies on three single nucleotide polymorphisms (SNPs): rs767649 (T > A), rs928883 (G > A), and rs1893650 (T > C). Meta-analysis was performed using RevMan 5.4, with odds ratios (ORs) and 95% confidence intervals (CIs) as effect measures.ResultsNo significant association was observed for rs767649 and rs928883 in overall cancer analysis. However, subgroup analysis revealed rs767649 increased susceptibility to respiratory, digestive, and reproductive cancers, while reducing cancer risk after excluding reproductive cancers. rs928883 showed a protective effect for digestive cancers. rs1893650 was not significantly associated with cancer risk.ConclusionMIR155HG polymorphisms influence susceptibility to specific cancer subtypes, particularly respiratory and digestive cancers. These findings underscore the importance of genetic and environmental factors in cancer risk and warrant further investigation.